Sistem Pakar Konsultasi Penyakit Diare berbasis Web menggunakan Metode Certainty Factor - Rahmawati, Rahmawati; Nurwati, Nurwati; Rohminatin, Rohminatin (Jurnal Pendidikan Informatika (EDUMATIC), 2024)
Many patients seek treatment at Dr. Hariyati Wahyuni's clinic for diarrhea pain but there is only one doctor who handles the disease. This condition makes it difficult for the doctor's performance to work optimally due to limited resources in serving patients. To overcome this problem, an expert system is needed where this system can be used to consult diarrhea diseases quickly. The purpose of this research is to create an expert system using the Certainty Factor method. This research is a type of development using the waterfall model with the research stages consisting of analysis, design, implementation and system testing. The analysis stage is carried out to identify the needs used to be applied to this expert system. The design stage consists of usecase design, class diagram and interface design. Implementation and testing are done directly using black box testing to see the extent of the functionality of the system that has been created. The data collection techniques used were interviews and observations. Our findings show that the expert system we developed is an expert system using the web-based Certainty Factor method. This system was also successful in testing using black box testing, all system components have functioned properly so that this expert system can help the Dr. Hariyati Wahyuni Clinic as a system for diagnosing diarrheal diseases quickly and precisely.